Aucun Ecrivain Ne Cree EX Nihilo. Le Cas De Djungu Simba Kamatenda Dans LA Mangeoire - Mboyo Bopeko, Jean Marie (International Journal of Scientific Research and Management (IJSRM), 2023)
Focused on the borrowings that a writer endeavors to draw from his society, this study is situated within the framework of Congolese literature (DR) where the author, anxious to see his society plunged into disaster, unpacks the vices that constantly gnaw at it, in order to raise awareness among its fellow citizens.